Chornobyl: a History of the Past or a Demonstration. How Science Can Solve the Problems of the Future?! - Sokol, Y.; Minakova, K.; Petrov, S.; Radohuz, S.; Lazurenko, O.; Zaitsev, R.; Lavrova, I.; Sincheskul, O.; Ilyinskaya, O.; Shestopalov, O. V. (Serednyak T. K., 2019)
The possibilities of a well-known historical event as a starting point for teaching various scientific and technical aspects are shown. In particular, it is indicated how, as an example of the Chornobyl disaster, it is possible to elucidate in detail the principles of the work of the nuclear power engineering and the scientific basis of the processes that took place during and after the accident (based on sections of the school course of physics covering nuclear physics). It is also indicated for scientific discoveries and implementation, as well as engineering and technical solutions that were used during the elimination of the consequences of the accident. Thus, one man-made disaster allows us to disassemble this problem from the history of science and technology, physics, chemistry and ecology. Thus, this approach allows us to introduce the aspects of multidisciplinarity into learning, and to point out the interconnections of different types of sciences, which promotes a better understanding of the need for comprehensive development by students, and motivates the study of natural sciences [1–2].
Keywords: Chornobyl; nuclear physics; power engineering; history of science; chemistry; ecology; safety and health; STEM education